The Students’ Perception Of The Use Of Online English Dictionary At Grade XI Sman 1 Tembilahan Hulu - Sari, Sella Rizna; Amri, Samsul; Maizarah, Maizarah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Indragiri (UNISI), 2023)
This research is motivated by the lack of students now to use dictionary which the result from preliminary observations are most students use online dictionary than book dictionary when studying the English language. The researcher become curious about the students experiences in using online dictionary. Thus, this study aims to investigate about students perception on the use of online dictionary by using quantitative method. The sample in this study were 35 students of class XI MIPA 5 SMAN 1 Tembilahan Hulu. Sampling was carried out using cluster sampling technique. In collecting data, researchers used a questionnaire as a research tool. This questionnaire is used to find out how students perception of the Use of Online English Dictionary. The questionnaire used in the study was presented in 5 (five) alternatives, commonly known as the Likert Scale. The results showed that students' perception of the Use of Online English Dictionary fall into the high category. It proved that 35 students got that category as the highest average score was in indicator selection with a score 140, followed by indicator organization with a score 139. And then the average value of indicator interpretation with a score 148. So, the researcher can conclude that the use of online dictionary can increase students’ interest in learning English. Because online dictionary is faster and easier than book dictionary.